Pengantar sejarah kebudayaan Indonesia - R. Sukmono (Yayasan Kanisius, 1973)
ir, jil.2,c.1-3/ast jil.1 =c.1-3 jil.2 =c.4-7 jil.3 =c.1/ tr, jil.3=c.2/ast, jil.1 =c.4, jil.2 =c.8/ir,jil.1,c.5/ad, jil.3,c.3